Heterosis and combining ability for nutritional quality in bottle gourd (Lagenaria siceraria) - BHATT, RAJENDRA; RAGHAV, MANOJ; BISHT, YASHPAL SINGH; KUMAR, VINAY; CHAUHAN, ARVIND; GAUR, AMIT (The Indian Journal of Agricultural Sciences, 2023)
The study was carried during kharif 2021 and zaid 2022 at Vegetable Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to investigate the nutritional properties of bottle gourd [Lagenaria siceraria (Molina) Standl] across various genotypes and hybrid combinations. Bottle gourd, a versatile crop with nutritional benefits, was analysed for traits like dry matter content, ascorbic acid, reducing sugar, non-reducing sugar, total sugar and total soluble solids. Promising parent genotypes, P6, P1 and P4 were identified based on their per se performance. The hybrid combination P2 × P7 exhibited exceptional results considering relative heterosis, heterobeltiosis and standard heterosis. Parent P3 demonstrated strong general combining ability for several traits. Notably, specific combining ability analysis identified hybrids like P2 × P6, P5 × P6, and P1 × P4 as promising for multiple traits. The prevalence of significant σ2SCA values over σ2GCA values highlighted the dominance gene action’s role in governing these traits, suggesting the potential of hybrid breeding for genetic enhancement. In conclusion, the study emphasizes the importance of nutrient quality and presents strategies for harnessing hybrid breeding to improve these traits in bottle gourd.